Mauritius : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mauritius. (IMF Staff Country Reports; Country Report, 2006)
Mauritius showed slow economic growth owing to the deteriorating external economic environment, particularly of the sugar and textile sectors. Executive Directors urged the authorities to develop a comprehensive economic strategy that combines structural reform measures and policies geared toward macroeconomic stability. They commended the financial sector reform and the implementation of Financial Sector Assessment Program recommendations, welcomed the financial sector monitoring and tax reforms plans and emphasized the need for strong exchange rate and monetary policies for securing external competitiveness.